Pengaruh Model Pembelajaran Kooperatif Tipe Diskursus Multy Reprecentacy (DMR) terhadap Hasil Belajar Matematika - Febrianti, Nadila; Rusdi, Rusdi; Rahmi, Ulva; Rahma, Tasnim (Universitas Cokroaminoto Palopo, 2026)
The poor performance of eighth grade mathematics students of SMP Negeri 4 Bukittinggi became the driving force of this study. Continued reliance on traditional teacher-centered forms of education is a major contributor. The purpose of this study was to determine whether the paradigm of cooperative learning Multy Reprecentacy (DMR) can help students learn mathematics better. Using a static group comparison design, the study was a preparation for the experiment. Students from two randomly selected classes-Class VIII D as the experimental group and Class VIII F as the control group-formed the study sample. An educational assessment tool in the form of a test designed to measure learning outcomes. Minitab and T-test were used to analyze the data. According to the findings, the value of thitung= 2.34 is more than ttabel=1.67 and the value of k= 0.012 is less than 0.05. DMR-type cooperative learning models have a major impact on student math achievement. Compared to more traditional learning models, DMR models provide better results.